"Working out" the relationship between informal language contact and phrasal verb development of international students in the UK - Zhou, S (2022)
Study abroad (SA) has long been regarded as a learning environment that is beneficial to second language acquisition (SLA), especially in competencies related to social interactions (Kinginger, 2011). However, little is known about whether SA students make actual gains in domains of English they are typically exposed to outside of classroom settings such as phrasal verbs (PVs), and whether their informal language contact contributes to such development. To explore this relationship, this study investigates students’ PV development and informal language contact, to understand how they make use of the L2 exposure during SA.